DOES INTERNALISATION OF MORAL VALUES PREDICT ADOLESCENTS’ PROSOCIAL BEHAVIOUR AND LESS TOLERANCE TOWARDS ANTISOCIAL BEHAVIOUR? - Kromerova, Enrika; Šukys, Saulius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of the current qualitative cross-sectional design study was to examine relations between the internalisation of moral values and prosocial behaviour as well as tolerance towards antisocial behaviour in adolescence. A total of 385 adolescents (192 girls and 193 boys) aged 13 and 16 years (mean age = 14.6, SD = 1.11) completed the self-reported measures of moral values internalisation, adolescents’ prosocial behaviour, and tolerance towards antisocial behaviour. Girls scored significantly higher than boys on moral values internalisation and such prosocial behaviour types as altruism and help in emergency situations. Girls were significantly less tolerant towards antisocial behaviour. Multiple regression analysis showed that external and introjected value regulations were the significant predictors of altruistic behaviour. Only the identified regulation was a significant predictor of adolescents’ intention to help others in emergency situations. Adolescent tolerance towards antisocial behaviour was predicted by the identified and integrated value regulations. Overall, these findings reflected the importance of personal values, especially moral values for encouraging adolescents’ moral behaviour and intolerance towards antisocial behaviour of peers.